Patient–provider discussion about emotional and social needs, mental health outcomes, and benefit finding among U.S. Adults living with cancer. (7th May 2021) - Hong, Young‐Rock; Yadav, Sandhya; Suk, Ryan; Khanijahani, Ahmad; Erim, Daniel; Turner, Kea
Abstract: Background: A discussion about patient's nonmedical needs during treatment is considered a crucial component of high‐quality patient–provider communication. We examined whether having a patient–provider discussion about cancer patients' emotional and social needs is associated with their psychological well‐being. Methods: Using the 2016–2017 Medical Expenditure Panel Survey‐Experiences with Cancer Survivorship Supplement (MEPS–ECSS) data, we identified the cancer survivors in the United States (US) who reported having a detailed discussion about emotional and social needs during cancer care. We used multivariable logistic regression to assess the association between having a patient–provider discussion and the patients' psychological well‐being outcomes (depressive symptoms, severe psychological distress, and worrying about cancer recurrence/worsening condition) and benefit finding experience after a cancer diagnosis. Results: Among 1433 respondents (equivalent to 13.8 million cancer survivors in the US), only 33.6% reported having a detailed patient–provider discussion about their emotional and social needs. Having a discussion was associated with 55% lower odds (odds ratio [OR], 0.45; 95% confidence interval [CI], 0.26–0.77) of having depressive symptoms and 97% higher odds (OR, 1.97; 95% CI, 1.46–2.66) of having benefit finding experience. There was no statistically significant association between patient–provider discussion and psychological distress or worrying about cancer recurrence/worsening. Conclusion: Detailed patient–provider discussion about the cancer patients' emotional and social needs was associated with a lower likelihood of depressive symptoms and a higher likelihood of experiencing benefit finding. These findings stress the importance of improving the patient–provider discussion about psychosocial needs in cancer survivorship. Abstract : Effective patient–provider communication is an integral part of delivering high‐quality cancer care. Study findings suggest that patient–provider discussions about emotional and social needs have a positive impact on mental health outcomes and attitudes toward cancer.